2013
DOI: 10.25200/bjr.v9n2.2013.543
|View full text |Cite
|
Sign up to set email alerts
|

Does community participation set the local press agenda? A view on deliberative and civic practices in the Portuguese press

Abstract: RESUMO -Que perceção têm os jornalistas sobre o papel dos cidadãos na vida democrática? Qual é o papel que os jornalistas atribuem ao público na construção da agenda informativa? O principal objetivo deste estudo é investigar a relação entre a imprensa local, os cidadãos e as práticas cívicas. Toma como ponto de partida uma abordagem teórica dupla -a teoria da democracia deliberativa e o movimento do jornalismo público -para avaliar o alcance de uma conceção de "jornalismo deliberativo." No âmbito do projecto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Asking journalists to share decision-making power or simply listening to ordinary people has never been easy: "sometimes it seems like a losing battle" (Witt, 2004, p. 51). A recent empirical study of local Portuguese media (Ferreira, 2013) has revealed how news organizations offering avenues for public involvement, at the same time, seek ways to protect the journalist's professional status. Data from this study show that, while professionals, especially in the regional context, acknowledge that they often receive contacts from ordinary citizens, most journalists devalue them, giving a preferential approach to elites, to the detriment of ordinary individuals.…”
Section: Final Notes: Transformations and Continuities Of A Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asking journalists to share decision-making power or simply listening to ordinary people has never been easy: "sometimes it seems like a losing battle" (Witt, 2004, p. 51). A recent empirical study of local Portuguese media (Ferreira, 2013) has revealed how news organizations offering avenues for public involvement, at the same time, seek ways to protect the journalist's professional status. Data from this study show that, while professionals, especially in the regional context, acknowledge that they often receive contacts from ordinary citizens, most journalists devalue them, giving a preferential approach to elites, to the detriment of ordinary individuals.…”
Section: Final Notes: Transformations and Continuities Of A Professionmentioning
confidence: 99%
“…Nevertheless, the results show a conventional journalistic stance that persists, evidenced mainly by low levels of relevance attributed to the functions associated with participatory journalism and by the valorization of functions associated with conventional journalism. These results in the production of journalistic contents too focused on elites and on commercial concerns (see Ferreira, 2013).…”
Section: Final Notes: Transformations and Continuities Of A Professionmentioning
confidence: 99%